Identifikasi Kerusakan Tanaman Cengkeh yang Disebabkan oleh Penggerek dengan Metode Rapid Assessment di Desa Paninggaran, Kecamatan Paninggaran, Kabupaten Pekalongan - Maudy Susanti; Irvan Zidni; Dwi Putro Tejo Baskoro (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Clove is a scented dried flower stalk from the Myrtaceae tree family. Farmers in Paninggaran Village experienced a problem, namely a decrease in clove production and even crop death. Dead molt is one of the diseases that are affected by clove plants and is related to the cultivation carried out by farmers in treating clove plants. Therefore, it is necessary to do a rapid assessment and checking to identify diseases in cloves and provide an explanation to farmers regarding symptoms and efforts to overcome this problem. The purpose of the rapid assessment and clove inspection activities is to analyze the knowledge, attitudes and actions of farmers in clove cultivation and to find out the right solution that can be done as an effort to respond to the incidence of molting on cloves. The method used is interviews and direct observation. Interviews were conducted with 9 farmers with direct observation of 20 clove trees. The result of this activity is the use of organic fertilizer by farmers still needs to be increased. Percentage of trees showing symptoms of stem and twigs by 4%, while trees showing symptoms of stem cancer by 96%. Farmers replace their commodities into tea as a solution so that the borers do not attack again. Knowledge, attitudes and actions of farmers in clove cultivation still need to be improved in order to minimize the negative impacts that will occur. Keywords: borers, clove cultivation, farmers, molt death, rapid assessment